Initiation of Grape (Vitis vinifera L.) on Different Sterilization Techniques - Ratu Mentari Dewi; Ramal Yusuf; Sri Anjar Lasmini; Hawalina Hawalina (Universitas Tadulako, 2018)
The most crucial step during the development of tissue culture is the method of explant sterilization. Especially, explants is sourced directly from fields that were more susceptible to microbial contaminations. This study aimed to obtain sterilization technique from several sterilant for reduced contamination and support growth of shoots grape in vitro. This research was conducted at the Laboratory of Plant Biotechnology, Faculty of Agriculture, University of Tadulako, during January to April 2018. The study used a factorial completely randomized design, one factor was tested i.e S1 = Taft 8,3 g/L (0,1% carbendazim), S2 = taft 25 g/L (0,3% carbendazim), S3 = taft 41,67 g/L (0,5% carbendazim), S4 = Taft 8,3 g/L (0,1% carbendazim) + HgCl2 0,1%, S5 = Taft 25 gr/L (0,3% carbendazim) + HgCl2 0,1% dan S6 = 41,67 gr/L (0,5% carbendazim) + HgCl2 0,1 %. There were six treatment and each treatment was replicated three times to obtain 18 experimental units. Each experimental unit using two explant. Data were analyzed using analysis of variance and followed by Honestly Significant Difference test at level of 5% if the treatment effects were significant. The results showed sterilization technique using taft 41,67 gram / L containing 0.5% carbendazim for 30 minutes, followed by 70% alcohol for 30 seconds and HgCl2 0,1% for 10 minutes gave free contamination for explant.whereas, Taft 8.3 g / L (Carb 0.1%) for 30 min, followed by 70% alcohol for 30 seconds is a sterilization technique that does not inhibit explant growth as indicated from the most callus formation.